Colchicine in Acute Myocardial Infarction - Jolly, Sanjit S; d'Entremont, Marc-André; Lee, Shun Fu; Mian, Rajibul; Tyrwhitt, Jessica; Kedev, Sasko; Montalescot, Gilles; Cornel, Jan H; Stanković, Goran; Moreno, Raul; Storey, Robert F; Henry, Timothy D; et al. (The New England journal of medicine, 2025)
BACKGROUND: Inflammation is associated with adverse cardiovascular events. Data from recent trials suggest that colchicine reduces the risk of cardiovascular events. METHODS: In this multicenter trial with a 2-by-2 factorial design, we randomly assigned patients who had myocardial infarction to receive either colchicine or placebo and either spironolactone or placebo. The results of the colchicine trial are reported here. The primary efficacy outcome was a composite of death from cardiovascular causes, recurrent myocardial infarction, stroke, or unplanned ischemia-driven coronary revascularization, evaluated in a time-to-event analysis. C-reactive protein was measured at 3 months in a subgroup of patients, and safety was also assessed. RESULTS: A total of 7062 patients at 104 centers in 14 countries underwent randomization; at the time of analysis, the vital status was unknown for 45 patients (0.6%), and this information was most likely missing at random. A primary-outcome event occurred in 322 of 3528 patients (9.1%) in the colchicine group and 327 of 3534 patients (9.3%) in the placebo group over a median follow-up period of 3 years (hazard ratio, 0.99; 95% confidence interval [CI], 0.85 to 1.16; P = 0.93). The incidence of individual components of the primary outcome appeared to be similar in the two groups. The least-squares mean difference in C-reactive protein levels between the colchicine group and the placebo group at 3 months, adjusted according to the baseline values, was -1.28 mg per liter (95% CI, -1.81 to -0.75). Diarrhea occurred in a higher percentage of patients with colchicine than with placebo (10.2% vs. 6.6%; P<0.001), but the incidence of serious infections did not differ between groups. CONCLUSIONS: Among patients who had myocardial infarction, treatment with colchicine, when started soon after myocardial infarction and continued for a median of 3 years, did not reduce the incidence of the composite primary outcome (death from cardiovascular causes, recurrent myocardial infarction, stroke, or unplanned ischemia-driven coronary revascularization). (Funded by the Canadian Institutes of Health Research and others; CLEAR ClinicalTrials.gov number, NCT03048825.).
Keywords: Recurrence; Male; Kaplan-Meier Estimate; cévní mozková příhoda; sekundární prevence; Kaplanův-Meierův odhad; C-reaktivní protein; Stroke; Aged; mužské pohlaví; senioři; Secondary Prevention; recidiva; infarkt myokardu; Spironolactone; dvojitá slepá metoda; lidé; ženské pohlaví; Humans; Colchicine; Myocardial Infarction; kolchicin; C-Reactive Protein; Double-Blind Method; Female; spironolakton; lidé středního věku; Middle Aged